2017
DOI: 10.1038/srep39706
|View full text |Cite
|
Sign up to set email alerts
|

The PPE2 protein of Mycobacterium tuberculosis translocates to host nucleus and inhibits nitric oxide production

Abstract: Mycobacterium tuberculosis, the bacterium that causes tuberculosis, is one of the most successful pathogens of humans. It has evolved several adaptive skills and evasion mechanisms to hijack the immunologically educated host to suit its intracellular lifestyle. Here, we show that one of the unique PPE family member proteins of M. tuberculosis, PPE2, can limit nitric oxide (NO) production by inhibiting inos gene transcription. PPE2 protein has a leucine zipper DNA-binding motif and a functional nuclear localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 49 publications
3
56
0
Order By: Relevance
“…However, the SNV in MprA* does not map in this region. (Bhat et al, 2017). Rv3423.1, a mycobacterial histone acetyltransferase, is known to co-localize with chromatin in macrophage nucleus while it was secreted into the culture medium by the virulent strain of the bacteria (Jose et al, 2016).The authors demonstrated that Rv3423.1 protein localizes with the chromatin and brings about histone acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the SNV in MprA* does not map in this region. (Bhat et al, 2017). Rv3423.1, a mycobacterial histone acetyltransferase, is known to co-localize with chromatin in macrophage nucleus while it was secreted into the culture medium by the virulent strain of the bacteria (Jose et al, 2016).The authors demonstrated that Rv3423.1 protein localizes with the chromatin and brings about histone acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…PPE2 imitates a eukaryotic transcription factor by the classical importin a/b pathway, binds to upstream regulatory sequences of inducible nitric oxide synthase (iNOS), and regulates iNOS transcription. PPE2 may aid the bacteria to suppress NO production (Bhat et al, 2017). Diverse roles of PE/PPE protein in the host immunity are summarized in Figure 2.…”
Section: Pe/ppe Proteins Imitate a Eukaryotic Transcription Factor Thmentioning
confidence: 99%
“…The Proline-Proline-Glutamate (PPE) family of proteins are particularly abundant in pathogenic Mycobacterial species such as Mtb (Bhat et al, 2017 ). Recent evidence indicates that these proteins can act as repressive transcription factors in the nucleus of host macrophages to suppress NOS2 expression and thereby reduce the release of the anti-mycobacterial NO molecule (Bhat et al, 2017 ).…”
Section: Mechanisms Of No-mediated Mtb Killingmentioning
confidence: 99%
“…The Proline-Proline-Glutamate (PPE) family of proteins are particularly abundant in pathogenic Mycobacterial species such as Mtb (Bhat et al, 2017 ). Recent evidence indicates that these proteins can act as repressive transcription factors in the nucleus of host macrophages to suppress NOS2 expression and thereby reduce the release of the anti-mycobacterial NO molecule (Bhat et al, 2017 ). In addition, soon after Mtb infection, macrophages produce IL-10 which induces the phosphorylation and activation of the transcription factor signal transducer and activator of transcription (STAT3) (Queval et al, 2016 ).…”
Section: Mechanisms Of No-mediated Mtb Killingmentioning
confidence: 99%